2019
DOI: 10.3389/fpls.2019.00856
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Limitation Improved Salt Tolerance in Maize Through Tissue Mass Density Increase, Osmolytes Accumulation, and Na+ Uptake Inhibition

Abstract: Low phosphorus (P) availability and salt stress are two major constraints for maize ( Zea mays L.) growth in north China. A combination of salinity and high P rather than low P is more detrimental to the growth of maize. However, little is known about the mechanisms by which P nutrition modifies the salt tolerance and P uptake of maize. The present study aimed to investigate the combined effects of salinity and P on maize growth and P uptake, and to address the physiological mechanisms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 67 publications
(83 reference statements)
3
59
1
Order By: Relevance
“…Present study also shows clustering of roots under P deprived conditions both in presence and absence of RAR, well correlated with higher phosphatase activity. However, under salinity alone and combined stress (P starved-salinity) conditions, lesser number of lateral roots accompanied with lesser root density is contrary to the report of Tang et al 53 . ABA, as a potential chemical signals in auxin independent manner is known to modulate the root system architecture under water stress 54,55 .…”
Section: Discussioncontrasting
confidence: 84%
“…Present study also shows clustering of roots under P deprived conditions both in presence and absence of RAR, well correlated with higher phosphatase activity. However, under salinity alone and combined stress (P starved-salinity) conditions, lesser number of lateral roots accompanied with lesser root density is contrary to the report of Tang et al 53 . ABA, as a potential chemical signals in auxin independent manner is known to modulate the root system architecture under water stress 54,55 .…”
Section: Discussioncontrasting
confidence: 84%
“…One SNP located on chromosome 1 (S1_1910174), control expression of serine/threonine-protein phosphatase PP1 isozyme 9, was identified to be significantly associated with dry weight affected by salt stress (Table 4, Figure 3). Previous studies reported a negative relationship between salinity level and phosphorus metabolism in plant roots and/or shoots [7,45,46]. However, an increase in phosphatase and ATPase activities have been observed in both roots and shoots under salt stress [19,45].…”
Section: Gwas Analysis Of Seedling Germination Traits Under Salt Stressmentioning
confidence: 91%
“…In general, salinity stress is one of the most harmful abiotic stresses affecting plant growth. Crop production in approximately 20% of the world's arable lands and nearly half of irrigated lands is adversely affected by salinity stress [6,7]. One of the effects of salinity stress is the inhibition of plant photosynthesis and growth by reducing water availability or osmotic stress, ion (Na + and Cl − ) toxicity, nutritional disorders and oxidative stress [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some amino acids play an adaptive role in mediating osmotic adjustment and protecting subcellular structure (He et al 2015). Proline can remove ROS and alleviate their effects on cell proteins and membranes (Tang et al 2019). Comparing the two maize genotypes revealed higher tendencies for the upregulation of proline in the roots of 'PH6WC', which testifies that NaCl stress can induce salt-tolerant maize to accumulate more proline to reduce membrane damage.…”
Section: Discussionmentioning
confidence: 90%